Clinical characteristics and outcomes of Stanford type B aortic intramural hematoma: A single centre experience - Zhang, Zhigong; Lin, Feng; He, Zhipeng; Wang, Haoran; Zhu, Xingyang; Cheng, Tingting (Frontiers in Surgery, 2023)
Objective: To compare the clinical characteristics of Stanford type B aortic intramural hematoma (IMH) and Stanford type B aortic dissection (AD), and to identify the differences between thoracic endovascular aortic repair (TEVAR) and medical management (MM) in the Stanford type B IMH patients. Methods: A retrospective observational study was conducted in patients treated between January 2015 and December 2016. The clinical characteristics and CT images of patients with type B IMH and type B AD were compared, and the clinical characteristics and CT images of patients in the type B IMH group who were treated with TEVAR and MM were compared. Results: A total of 176 patients were included in this study, including 62 patients of type B IMH and 114 patients of type B AD. Five patients died in the IMH group and three in the AD group. The proximal hematoma or entry tear in both groups was mainly located in the descending aorta, and the proportion of the iliac artery involved in the AD group was significantly higher than that in the IMH group (31.6% vs. 8.1% P < 0.05). There were 50 MM patients and 12 TEVAR patients in the IMH group. No death occurred in the TEVAR group, while five patients in the MM group died. Seven patients in the MM group had disease progression versus 12 in the TEVAR group (P < 0.05). The patients in the TEVAR group had more intima lesions than those in the MM group (83.3% vs. 30.0%, P < 0.05). TEVAR group involved more iliac artery hematoma than MM group (33.3% vs. 2.0%, P < 0.05). The maximum thickness of hematoma in TEVAR group was 14.9±3.4mm, which was significantly larger than that of MM group (10.2±2.8mm) (P < 0.05). Conclusion: In the diagnosis of IMH, patients' symptoms and high-risk signs of CTA should be paid attention to. TEVAR therapy should be actively considered on the basis of effective medical management when there are intima lesions (ULP/PAU), increased aortic diameter and hematoma thickness, extensive hematoma involvement, and pleural effusion.